Melawan Arus Modernisasi: Eksistensi Islam Aboge di Desa Sumbersuko, Probolinggo (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to understand how the Aboge Islamic community in Sumbersuko Village maintains its existence amid modernization, which tends to promote uniformity in religious practices. This research employs a qualitative approach with an ethnographic method. The researcher acts as the main instrument, and data were collected through in-depth interviews, participant observation, and documentation. The data were analyzed inductively through data reduction, data presentation, and drawing conclusions. The study focuses on three aspects: first, understanding Aboge Islam as a form of religious expression intertwined with local culture; second, exploring the function of the Aboge calendar as a timekeeping system rich in spiritual meaning and cultural identity; third, analyzing the practice of the collective tradition of Jumat Legi Night as a means of strengthening internal solidarity and building inclusive social relationships. The findings show that the Aboge Islamic community successfully preserves its traditions by developing adaptive strategies rooted in ancestral values while remaining open to wider social interaction. Their religious practices serve not only as cultural resistance but also as a unifying force in the midst of social change.